Pemberdayaan Petani melalui Produksi Mikroorganisme Lokal (MOL) dan Plant Growth Promoting Rhizobacteria (PGPR) untuk Meningkatkan Produktivitas Padi dan Silase di Desa Kemiri, Kabupaten Jember - Tanzil, Ahmad Ilham; Muhlison, Wildan; Saputra, Tri Wahyu; Rahayu, Puji; Yulianto, Roni; Anantoro, Tri; Hadi, Yusnan; Alfarisy, Fariz Kustiawan; Pusparani, Syafina; Rachmandhika, Yusuf; Syahputra, Wahyu Nurkholis Hadi (Universitas Nusantara PGRI Kediri, 2025)
Kemiri Village, Panti District, Jember Regency is one of the rice-producing villages but faces the problem of scarcity of subsidized fertilizers and ineffective management of agricultural waste. This needs to be overcome with simple but effective handling. This community service activity aims to empower farmers through the production of Local Microorganisms (MOL) and Plant Growth Promoting Rhizobacteria (PGPR) to increase rice productivity while supporting the potential of livestock in the village. The target partner in this activity is the Sidodadi farmer group consisting of 30 farmers. The implementation method includes training in making MOL and PGPR, applying PGPR to rice plants, and making silage as animal feed. The results of the activity show that the activities carried out related to the use of PGPR can help increase rice growth, improve yields, and reduce dependence on chemical fertilizers. In addition, making silage successfully processes green fodder into quality feed that supports food security for livestock in the village. In the future, this activity is expected to strengthen the sustainability of agricultural and livestock practices in Kemiri Village and improve the economy of farmers.